Punishing (Not)Innocent Persons? - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
This article provides a critical analysis of Mark Walker’s type-token theory. This theory purports to describe, explain, and justify the mechanism by which moral and legal responsibility can be attributed to exact and complete duplicates of persons. However, Walker’s defence of the view of persons as abstract entities is met with several metaphysical objections. Alternatively, a new approach to moral and legal responsibility is developed based on principles of agency law, in which the conception of a guilty person does not require identity with the person who committed the culpable act.